2016
DOI: 10.18632/oncotarget.13512
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical investigating the predictive value of p53, COX2, EGFR, nm23 in the post-operative patients with colorectal carcinoma

Abstract: The aim of this study was to evaluate the correlations between p53, COX2, EGFR, nm23 expression and the progression free survival (PFS) of post-operative patients with colorectal carcinoma. Immunohistochemistry was used to detect the expression of p53, COX2, EGFR and nm23 in 459 specimens from colorectal carcinoma patients. Kaplan-Meier estimates, Cox proportional hazard regression analyses and hierarchical analyses were performed on the collected data. Kaplan-Meier estimates analysis suggested that EGFR expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…Considering that both pro-invasive and anti- metastatic roles of c-Myb were described, we examined the expression of c-Myb at protein level in 202 CRC tissue samples and verified it at mRNA level using public databases from The Cancer Genome Atlas (TCGA) cohort of patients with colon adenocarcinoma (TCGA COAD). In agreement with the reported studies9,22,27, we found that the expression of c-Myb (p < 0.001), detected by IHC, was significantly higher in the CRC tissues in comparison with the adjacent normal tissues. Meanwhile, elevated expression of c-Myb was significantly associated with more advanced tumor invasion (p = 0.020), higher TNM stage (p = 0.019) and poorer overall survival (p < 0.001).…”
Section: Discussionsupporting
confidence: 93%
“…Considering that both pro-invasive and anti- metastatic roles of c-Myb were described, we examined the expression of c-Myb at protein level in 202 CRC tissue samples and verified it at mRNA level using public databases from The Cancer Genome Atlas (TCGA) cohort of patients with colon adenocarcinoma (TCGA COAD). In agreement with the reported studies9,22,27, we found that the expression of c-Myb (p < 0.001), detected by IHC, was significantly higher in the CRC tissues in comparison with the adjacent normal tissues. Meanwhile, elevated expression of c-Myb was significantly associated with more advanced tumor invasion (p = 0.020), higher TNM stage (p = 0.019) and poorer overall survival (p < 0.001).…”
Section: Discussionsupporting
confidence: 93%
“…In Guangxi, the male and female liver cancer mortality was 69.0/100,000 and 17.9/100,000 respectively, which was the highest fatality rate for male and female patients in China [6]. Epidemiological studies showed that the major risk factors for liver cancer in Guangxi included three major risk factors: hepatitis viruses (especially HBV), aflatoxin (AFB) intake, and drinking water source pollution [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Ezrin protein is a member of the cytoskeletal cross-linked protein ERM, which mainly mediates the connective function of membrane and cytoskeleton with a series of functions for relevant cells ( 17 ). The excessive expression and activation of Ezrin can lead to abnormal intercellular signal transmission and promote tumor cell metastasis, thus playing a role in tumor invasion and metastasis ( 18 , 19 ). Studies have shown that Ezrin protein is closely related to pulmonary metastasis of osteosarcoma patients, which can be used as an index of predicting the prognosis and survival ( 20 ).…”
Section: Discussionmentioning
confidence: 99%